War in international society - Pejcinovic, Lacy. (Milton Park, Abingdon, Oxon : Routledge, 2013)
"Is war an institution of international society and how is it constituted as such across the evolution of international society? This book is an inquiry into the purpose of war as a social institution, as originally put forward by Hedley Bull. It offers a comprehensive examination of what is entailed in thinking of war as a social institution and as a mechanism for order"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: War and society -- History; Electronic books